2012
DOI: 10.1007/s11356-012-1076-9
|View full text |Cite
|
Sign up to set email alerts
|

The legacy of persistent organic pollutants in Azerbaijan: an assessment of past use and current contamination

Abstract: Azerbaijan has a history of production and heavy use of organochlorine pesticides (OCPs) with use focused in the main agricultural lowland region centred on the Kur River. Using a number of data sources, including archived reports from several government ministries, we attempt to construct production and use inventories for dichlorodiphenyltrichloroethane (DDT) and HCHs and compare these to scientific estimates of production and use of these chemicals in the 1960s to the 1980s. Notable discrepancies are eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 31 publications
0
13
1
Order By: Relevance
“…[4,6,7,19,[25][26][27]. As mentioned before, the data reported by Aliyeva [28] from Azerbaijan were much lower than our results, but these studies were carried out in other area of Azerbaijan. According to Li et al [29], the total amount of DDTs used in the Azerbaijan in the years 1946-1990 was assessed as 250,000-520,000 tones.…”
Section: Assessment Of Ocps Concentrations In Soilscontrasting
confidence: 62%
See 2 more Smart Citations
“…[4,6,7,19,[25][26][27]. As mentioned before, the data reported by Aliyeva [28] from Azerbaijan were much lower than our results, but these studies were carried out in other area of Azerbaijan. According to Li et al [29], the total amount of DDTs used in the Azerbaijan in the years 1946-1990 was assessed as 250,000-520,000 tones.…”
Section: Assessment Of Ocps Concentrations In Soilscontrasting
confidence: 62%
“…The concentrations of Σ3HCHs were much lower than those observed for DDTs and ranged from 0.1 × 10 −4 µg kg −1 to 166.7 µg kg −1 . Alyieva et al [28] reported lower concentrations of HCH in soils in Azerbaijan, varying in the range 0.9 × 24.5 µg kg −1 . The dominant compound was α-HCH, which contributed about 73 % of the Σ3HCHs, followed by β-HCH and γ-HCH ( Table 1).…”
Section: Assessment Of Ocps Concentrations In Soilsmentioning
confidence: 99%
See 1 more Smart Citation
“…These transport routes are primarily initiated during heavy precipitation events and lead to transient peak concentrations often exceeding current ecological quality criteria (Bundschuh et al 2014;Liess and von der Ohe 2005;Schulz 2004). In contrast, legacy pesticides may enter surface water continuously via groundwater inflow (Barth et al 2007;Gilliom 2007;McKnight et al 2015), atmospheric deposition (Konstantinou et al 2006;Weber et al 2010) or through continuous leaching from agricultural soils and landfills (Aliyeva et al 2013).…”
Section: Abstract: Legacy Pesticides Environmental Risk Assessment mentioning
confidence: 99%
“…Based on water samples mainly analysed for herbicides and four sediment samples mainly analysed for insecticides, McKnight et al (2015) suggested that legacy pesticides could still be prominent players driving observed impairments of freshwater invertebrates, and the authors urged for more extensive studies that allow for quantifying the predicted toxicological potency of legacy pesticides in comparison to current use pesticides. To our knowledge, such an extensive study of the potential toxicity of legacy pesticides to aquatic biota relative to that of contemporary pesticides is still lacking despite a substantial body of literature addressing the occurrence, concentrations and predicted toxicities of selected legacy pesticides (Aliyeva et al, 2013;Gilliom, 2007;McKnight et al, 2015;Weber et al, 2010). The novelty element is therefore to quantify the possible toxicity of legacy pesticides as an integral part of current risk assessment.…”
Section: Abstract: Legacy Pesticides Environmental Risk Assessment mentioning
confidence: 99%